2018
DOI: 10.3390/met8110964
|View full text |Cite
|
Sign up to set email alerts
|

Major Impediment to Highly Efficient, Stable and Low-Cost Perovskite Solar Cells

Abstract: Organic–inorganic hybrid perovskite solar cells (PSCs) have made immense progress in recent years, owing to outstanding optoelectronic properties of perovskite materials, such as high extinction coefficient, carrier mobility, and low exciton binding energy. Since the first appearance in 2009, the efficiency of PSCs has reached 23.3%. This has made them the most promising rival to silicon-based solar cells. However, there are still several issues to resolve to promote PSCs’ outdoor applications. In this review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 183 publications
0
16
0
Order By: Relevance
“…The problem of a noble metal top electrode is widely discussed currently in the literature on the perovskite‐based devices, especially in mesoscopic solar cells without buffer underlayers . One of the important issues here appears to be downward (vertical) diffusion of metal atoms into the bulk of a photoabsorber layer, which leads to instability and loss in the devices performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The problem of a noble metal top electrode is widely discussed currently in the literature on the perovskite‐based devices, especially in mesoscopic solar cells without buffer underlayers . One of the important issues here appears to be downward (vertical) diffusion of metal atoms into the bulk of a photoabsorber layer, which leads to instability and loss in the devices performance.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of Samples : The FAPbI 3 films were obtained by the vacuum codeposition technique according to Refs . with lead(II) iodide PbI 2 and FAI as precursors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…22. This particular choice is motivated by both the lack of underlying data available [78], and the many ongoing challenges related to the outdoor deployment of perovskite modules [79]. For example, Dupre et al [80] showed that a "thermal benefit" strongly depends on the global heat transfer mechanisms between the module and its (outdoor) surrounding.…”
Section: The Temperature Dependence Of a Mapi-si Tandem Cellmentioning
confidence: 99%